Deficiency in MT5-MMP Supports Branching of Human iPSCs-Derived Neurons and Reduces Expression of GLAST/S100 in iPSCs-Derived Astrocytes - Nikita Arnst; Pedro Belio-Mairal; Laura García-González; Laurie Arnaud; Louise Greetham; Emmanuel Nivet; Santiago Rivera; Alexander Dityatev (Cells, 2021)
For some time, it has been accepted that the β-site APP cleaving enzyme 1 (BACE1) and the γ-secretase are two main players in the amyloidogenic processing of the β-amyloid precursor protein (APP). Recently, the membrane-type 5 matrix metalloproteinase (MT5-MMP/MMP-24), mainly expressed in the nervous system, has been highlighted as a new key player in APP-processing, able to stimulate amyloidogenesis and also to generate a neurotoxic APP derivative. In addition, the loss of MT5-MMP has been demonstrated to abrogate pathological hallmarks in a mouse model of Alzheimer’s disease (AD), thus shedding light on MT5-MMP as an attractive new therapeutic target. However, a more comprehensive analysis of the role of MT5-MMP is necessary to evaluate how its targeting affects neurons and glia in pathological and physiological situations. In this study, leveraging on CRISPR-Cas9 genome editing strategy, we established cultures of human-induced pluripotent stem cells (hiPSC)-derived neurons and astrocytes to investigate the impact of MT5-MMP deficiency on their phenotypes. We found that MT5-MMP-deficient neurons exhibited an increased number of primary and secondary neurites, as compared to isogenic hiPSC-derived neurons. Moreover, MT5-MMP-deficient astrocytes displayed higher surface area and volume compared to control astrocytes. The MT5-MMP-deficient astrocytes also exhibited decreased GLAST and S100β expression. These findings provide novel insights into the physiological role of MT5-MMP in human neurons and astrocytes, suggesting that therapeutic strategies targeting MT5-MMP should be controlled for potential side effects on astrocytic physiology and neuronal morphology.